33 Strategi Perang = (The 33 strategics of war) Robert Greene ; alih bahasa, Arvin Saputra ; editor, Sigit Suryanto, Lyndon Saputra - GREENE, Robert; Saputra, Arvin; Suryanto, Sigit; Saputra, Lyndon (Karisma Publishing, 2007)
706 hlm 24 cm